2012
DOI: 10.1016/j.vetpar.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The combination of abundance and infection rates of Culicoides sonorensis estimates risk of subsequent bluetongue virus infection of sentinel cattle on California dairy farms

Abstract: Bluetongue is an important viral disease of ruminants that is transmitted by hematophagous Culicoides midges. We examined the seasonal patterns of abundance and infection of Culicoides sonorensis (C. sonorensis) at 4 dairy farms in the northern CentralValley of California to develop estimates of risk for BTV transmission to sentinel cattle at each farm. These 4 farms were selected because of their similar meteorological conditions but varying levels of vector abundance and BTV infection of cattle (Mayo et al.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…Ongoing surveillance since that time, including our studies, has confirmed that BTV infection of ruminant livestock in California is endemic but highly seasonal (late July – November), thus the interseasonal period (November – July) when BTV is apparently “inactive” lasts approximately 8 months [9], [15], [16], [17]. In the current study we undertook intensive surveillance of sentinel cattle and vector midges during both the seasonal and interseasonal periods of BTV activity at a dairy farm in Northern California (latitude 39.590° N).…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Ongoing surveillance since that time, including our studies, has confirmed that BTV infection of ruminant livestock in California is endemic but highly seasonal (late July – November), thus the interseasonal period (November – July) when BTV is apparently “inactive” lasts approximately 8 months [9], [15], [16], [17]. In the current study we undertook intensive surveillance of sentinel cattle and vector midges during both the seasonal and interseasonal periods of BTV activity at a dairy farm in Northern California (latitude 39.590° N).…”
Section: Introductionsupporting
confidence: 61%
“…Collection of adult midges was repeated during a portion of the interseasonal period of 2014 (January-March) on the transect where 32 parous females had been collected in 3 different traps during Feb 2013, and on another transect where no interseasonal activity of midges was detected during 2013. Trapping was performed weekly in 2014 with the addition of 3 tent - type emergence traps set and rotated weekly along the edge of the waste-water lagoon, a known larval habitat [9]. The emergence traps were constructed of no-seeum netting (Bioquip Products) securely fastened over polyvinyl chloride (PVC) pipe.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations